Geographic Distribution of DHF Cases and Larvae Free Index In Situbondo Regency, 2019-2021 - Nurmayanti, Demes; Mukarromah, Hanifah Nailul; Marlik, Marlik; La Ane, Ruslan (Media Kesehatan Masyarakat Indonesia, 2023)
For the last 3 years of dengue cases in Situbondo Regency, there were 475 patients recorded from January to December 2021 (incident rate, IR = 68.904/100,000) and 4 death cases (case fatality rate, CFR = 0.8%). The average percentage of Larvae Free Index Situbondo scores is still below the Environmental Health Quality Standards for an area of ​​at least 95%. This study aims to describe the mapping of Larvae Free Index and dengue cases in Situbondo district in 2021. The type of this research is descriptive. The object of this research is the value of Larvae Free Index and cases of DHF. The data obtained is secondary data from Larvae Free Index and DHF cases in Situbondo Regency for 3 years starting from 2019-2021. The data is displayed using QGIS mapping using points and polygons. Health information and the potential for dengue fever in the area can be identified using geographic mapping, this information can be used to decide policies in breaking the chain of disease. The number of dengue cases in Situbondo Regency increased from 2019-2021. Larvae Free Index value of each village is better than the previous year. The spread of dengue cases is very high due to the mobility of residents who carry out activities outside the area of residence, resulting in transmission of dengue through mosquito bites. To prevent the spread of dengue cases, people are expected to use mosquito-repellent lotion when traveling.